Physicochemical properties of palm olein based on cloud point value - Puji, Lestari; Nerdy, Nerdy; Faisal, Yusuf; Firdaus, Fahdi (Journal of Midwifery and Nursing, 2024)
Palm olein is processed from the fruit of the oil palm (Elaeis guineensis) and used as cooking oil. Olein is widely used for frying in many countries. Therefore, the objective of this study was to research the physicochemical properties of palm olein based on cloud point value and compare the result with PORAM (The Palm Oil Refiners Association of Malaysia) standard and SNI 7709:2019 . The iodine values (IV), peroxide values (PV), free fatty acid (FFA) are often considered to be major significance indexes for the assessment of quality and stability of oils. There were seven samples in total, based on CP value (CP 7.2, CP 7.6, CP 8.0, CP 8.4, CP 8.8, CP 9.2, and CP 9.6).  Quality characteristics iodine values (IV), peroxide values (PV), free fatty acid (FFA) of RBD palm olein were measured. Cloud point is related to iodine value. The higher IV, the lower will be the CP. CP is related to the unsaturation level of olein, the more unsaturated the olein, CP will be lower. CP is unrelated with PV and FFA value which the increase CP value has no effect on the PV and FFA value. The physicochemical properties (IV, PV, FFA) of olein CP 7.2, CP 7.6, CP 8.0, CP 8.4, CP 8.8, CP 9.2, and CP 9.6  is fulfil PORAM standard and SNI 7709:2019.